Teknologi oven anealling kaca tellurite berbasis mikrokontroller dengan bahan bakar bio-briket - Adi Pramuda; Lia Angraeni; Soka Hadiati (IKIP PGRI Pontianak, 2022)
The A process known as annealing is important for reducing stress in working optical materials. The problem that arises is that the annealing process requires a large amount of heat energy or total heat. The purpose of this research is to reveal the thermal stability curve of an oven with bio-briquette fuel that works at the average temperature of the annealing process; 2. To obtain the optimal value of the use of bio-briquette fuel at several set temperatures of the tellurite glass annealing process. This research uses laboratory experimental research methods. The results show that: preheating with a time of 8 minutes produces an average oven temperature above the bio-briquette coals of 418 oC. Oven with bio-briquette fuel that works stably at a temperature of 471 oC with a preheating time of 5 minutes; The modification results resulted in the oven's ability to heat stably at 363.6oC for 4 hours using three coconut shell bio-briquettes with a size of 2 x 1.5 x 1.5 cm.